The Omani Fleet During 1034H – 1162H: الأسطول العُماني من 1034 هـ وحتى 1162 هـ - al-Toobi, Ahmed Humaid; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2021)
This study aims to shed light on the Omani fleet during the Ya’rubids Dynasty that ruled Oman since the first half of the eleventh Hijri century (1034H) up to the second half of the twelfth Hijri century (1162H) and had successfully liberated Oman from the Portuguese grip of its coastal lines after over 140 years of the Portuguese domination. Moreover, the Ya’rubids Dynasty played a significant historical role in Jihad beyond the Omani territories as they extended valuable assistance to other nations in their struggle against the Portuguese. The Omani fleet was considered a resounding accomplishment of the Omani craftsmanship at that time. The researcher anticipates that this study will unveil the circumstances that driven the Oman to build, develop and deploy and provide a detailed description of the fleet and its power and prowess depending on the documentation of Arab and foreign sources. The importance of this study lies in showcasing the power and might of the Omani fleet as it attracted the attention and interest of so many stakeholders. Hence, the researcher will try his best to probe the various historical sources and references available including archives on the Ya’rubids Dynasty, particularly the Portuguese and other documents written by contemporary writers at that time about the Omani fleet. Further, the researcher will use the descriptive and analytical approach to reveal and compile the relevant facts.